POTENTIAL ANALYSIS OF SULFONATED PEG-DIOLEATE FOR CHEMICAL ENHANCED OIL RECOVERY (CEOR) APPLICATION - Lana Ferdiyansyah, Wahyu
National oil production tends to decrease from year to year, however national oil consumption always increases. The solution that can be propose to increase oil production is conducting Chemical Enhanced Oil Recovery (CEOR) with surfactant injection. Role of surfactants in reducing the interfacial tension of oil and water, with the result that increasing oil production. One of the surfactants that could be used in CEOR is sulfonated alkyl ester surfactant (SAE), which has interfacial tension of 10-3mN/m in formulated with FEO-18 (Fatty Ester Oleate C-18). The objective of this study was to modify SAE into Sulfonated PEG Dioleate (SPEGD), a gemini surfactant, to obtain an expected lower interfacial tension than SAE. In the pre-analysis of surfactants by measuring HLB (hydrophylic - Lyophylic Balance), SPEGD has a value of 11.93 or could form an oil-in-water emulsion, for that reason it will increase the ability of surfactants to sweep the oil. SPEGD was synthesized from the esterification reaction of oleic acid and PEG 400 followed by sulfonation using NaHSO3. The synthesized SPEGD was characterized by Thin Layer Chromatography (TLC), IR Spectroscopy, 1H NMR, and 13C NMR. The characterization results showed that SPEGD had been successfully synthesized, but there were still unreacted by-products and reactants. Compatibility tests such as solution stability tests, phase behavior tests and interfacial tension measurements were conducted on SPEGD to evaluate the performance of surfactants in CEOR application. As a result, SPEGD has a good kinerjance with an interfacial tension of 9.81 x 10-4mN/m at 4000 ppm salinity, 40? temperature, and an equivalent alkane carbon number of 18.